Alterations in desmosomal adhesion at protein and ultrastructure levels during the sequential progressive grades of human oral tumorigenesis. (15th June 2018) - Sawant, Sharada; Dongre, Harsh; Ahire, Chetan; Sharma, Shilpi; Jamghare, Sayli; Kansara, Yashvi; Rane, Pallavi; Kanojia, Deepak; Patil, Asawari; Chaukar, Devendra; Gupta, Sudeep; D'Cruz, Anil; et al.
Abstract : With the aim of developing early diagnostic/prognostic markers for oral cancer, desmosomal adhesion in sequentially progressive grades of tissues from oral normal/disorders (normal, hyperplastic, dysplastic, non‐metastatic/metastatic tumours, and metastatic nodes) was investigated at protein and ultrastructural levels using immunohistochemistry and transmission electron microscopy, respectively. The expression of desmosomal proteins was higher in hyperplastic tissues than in normal tissues but was significantly decreased in subsequent progressive stages of the disease. Altered expression of desmosomal proteins was significantly correlated with local recurrence and disease‐free survival. Ultrastructural analysis in the corresponding tissues revealed cytoplasmic clustering of desmosomes in hyperplasia; in more advanced disease stages, a significantly lower number of desmosomes and widened intercellular spaces were observed. Altered protein expression resulting in structural changes was confirmed by knocking down desmoplakin expression in non‐transformed cells, which failed to form normal desmosome structures and induced a cell‐transformation phenotype. Our data suggest that alterations in desmosomal assembly initiate at an early hyperplastic grade and, with more advanced disease stages, the severity of the alterations gradually becomes higher. Alterations in desmosomal adhesion can be useful for early detection of high‐risk premalignant lesions, as well as for identification of invasive characteristics of primary non‐metastatic tumours. Early detection will help to control further progression of disease by timely intervention.